(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The role of the state in the system of public procurement, placement of crops and control over agricultural production is enhanced by increasing labor productivity in farms and dekhkan farms, ensuring food safety and quality, protecting the environment and the private sector. managing the provision of public services required for other purposes not provided strengthening cooperation with the private sector in the provision of public services using public-private partnership mechanisms